THE REFORM OF THE ADMINISTRATIVE JUDICIARY IN AUSTRIA: A BRIEF PRESENTATION - Michal Novotný (Jurisprudencija, 2023)
The administrative judiciary in Austria was born between 1867 and 1876 via the creation of the Administrative High Court (Verwaltungsgerichtshof) and, until a short time ago, its structure remained generally intact. Following long-lasting discussions, a reform was passed in 2012, which brought about the creation of first-instance administrative courts, and which led to a change from a single-tier to a two-tier administrative judiciary. Effective as of 1 January 2014, in addition to the already existing Administrative High Court, the reform established two new administrative courts at the federal level and nine provincial administrative courts. These courts adjudicate in the first instance, while the Administrative High Court has become an appellate court. Simultaneously, the reform simplified the review procedures within public administration. The public administration bodies thus decide in one single instance only; their decisions are immediately reviewable by the administrative courts. Other effects of the reform include the abolishment of a vast number of quasi-judicial administrative bodies, which previously took the position of first-instance administrative courts. The following article briefly outlines important features of the legal framework for the administrative judiciary both before and after the reform. At the same time, it provides a brief overview of the impacts of the reform on the performance of administrative courts.